The marketing of all things - Carrero Márquez, Oliver (Journal of Management and Business Education, 2021)
In a context marked by a changing reality, where technology bursts in with increasing force and business models are increasingly disruptive, the university and marketing are faced with the challenge of adapting to future groups of professionals to the new demands. It is a text that tries to combine all the aspects that come together in the material and human development of a society that transfers the demand for a highly personalized treatment and that puts endless data, derived from their daily routines, collected thanks to the Internet of Things and that allows differentiating new lover profiles, paradoxically from their intimacy and who prefer to be identified by their psychological age and not by their numerical age. A point of view for which universities must be prepared and go further, since they must focus on the internationalization and social inclusion of workers, in light of the concepts of training and freedom.